Se é de paz pode chegar, entrar na roda e jogar: formação de educadores da Associação Zumbi Capoeira em cultura de paz - Dias, Lúcia Vanda Rodrigues (2016)
This study aimed to investigate to what extent the training Culture of Peace can contribute to the pedagogical practices of 20 educators from Zumbi Capoeira Association - AZC from inserting constituents of Education for Peace in their daily lives to teaching learning, contributing to building a culture of peace in society. It is a qualitative approach, with planned strategies consistent with the research intervention, among which highlighted the semi-guided interviews, participant observation, field diary and especially the workshops focused on culture of peace. The training process took place through 10 workshops that covered topics such as peace; human rights; non-violent resolution of conflicts; disarmament and security; history of capoeira context and its educational aspects. Highlight the reinterpretation of the concepts of peace and conflict, as initial contributions to the training process, providing participants with the creation of a sense of "positive peace" in that dialogue was appointed as a way to resolve conflict situations. After the training, the teachers of the AZC held shares in culture of peace in their respective educational centers, choosing the workshops as teaching strategies to educate for peace, organized from the needs ascertained in each teaching space. Nuclei in Bom Jardim and Hope actions were focused on deepening sense of peace, with the understanding of this concept linked to action; At the core Jardim Iracema the concept of conflict came to be understood as something natural and that can be solved peacefully, either by direct agreement or through mediation, where dialogue plays a fundamental role. At the core Canindezinho understanding of the culture of peace was worked linked to the environmental aspect, as for educators and students peace group will only be carried out with human awareness to care for the planet and the beings that compose it. Ceara Bar Core educators opted for revitalization of some human values implicit in the practice of capoeira that are components of an education in values and consequently an education for peace. A general action to include the theme culture of peace in the middle capoeirista was drawn and put into practice by linking AZC with the Sustainable Development Network of Capoeira in Ceará, which provided the partnership of 11 capoeira groups for peace at the event called Capoeira for peace. the practice of peace culture circles was also implemented in educational centers of AZC, leading their teachers to a broader view of their students, the reality of each and the general group, in addition to search press for a more harmonious and peaceful coexistence. The realization of this research points to the capoeira school as a place where peace can be taught and learned, as well as indicating the training in culture of peace as a fundamental strategy to expand training spaces committed to education for peace and multiply committed educators that assignment.